Stopping of the Downtrend of Tuberculosis in Iran, a Systematic Review of Associated Risk Factors - Fadaee, Manouchehr; Rashedi, Jalil; Arabi, Sepideh; Poor, Behroz M.; Kafil, Hossein Samadi; Pourostadi, Mahya; Kazemi, Abdolhassan; Asgharzadeh, Mohammad (Infectious Disorders - Drug Targets, 2020)
Tuberculosis (TB) is a public health problem in developing countries. In recent decades, the incidence of the disease has been gradually reducing in Iran. However, the reducing incidence of the disease has stopped in the country during recent years. It could be due to an increase in immigration, diabetes, HIV/AIDS, and the prevalence of drug-resistant strains. In order to prevent the spread of TB cases and control this disease, it is essential to identify the predisposing factors, which may be related to bacteria, host and environment. The objective of the present systematic review was to investigate the role of potentially effective factors in the increase in TB cases in the country. The epidemiological studies that had considered the risk factors for the development of TB in populations from different regions of Iran were reviewed systematically from the beginning of 2007 to the end of June 2017 in electronic databases. Upon evaluation of the literature, these 7 major risk factors were identified in twenty-five eligible studies, including poor living conditions, drug abuse, HIV/AIDS, multidrug-resistant tuberculosis (MDR-TB), diabetes, migration, and smoking. In conclusion, the increase in predisposing risk factors for catching TB, especially the migration and Beijing strain, shows that in the absence of accurate monitoring, TB cases will increase in the near future in Iran.
Keywords: Tuberculosis